Probiotics and prebiotics in foods : challenges, innovations, and advances - Cruz, Adriano Gomes da; Ranadheera, Senaka; Nazzaro, Filomena; Mortazavian, Amir (Academic Press, 2021)
Probiotic and Prebiotics in Foods: Challenges, Innovations, and Advances reviews recent advances, innovations, and challenges in probiotics/prebiotics in food and beverages. The book presents up-to-date, novel and extensive information regarding recent research and applications in probiotics and prebiotics in food. Sections address probiotics, prebiotics, paraprobiotics and postbiotics, probiotics, prebiotics and bucal health, probiotics, prebiotics and obesity, probiotics, prebiotics and sleep quality, in vitro and in vivo assays for selection of probiotics, probiotics and mycotoxins, edible films added to probiotic and prebiotics, predictive microbiology applied to development of probiotic foods, non-bovine milk products as probiotic and prebiotic foods, emerging technologies, and much more. Written for food scientists, nutritionists, health professionals, food product developers, microbiologists, those working in food safety, and graduate students and researchers working in academia, this book is a welcomed resource on the topics discussed.